Association of Perceived Benefits and Ease of Use on Quality of Palopo City Government Information System Through User Satisfaction - Sahrial Pirham; Muammar Khaddapi; Rahmawati Rahmawati (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: The use of effective and quality information systems is very important in improving organizational performance. However, the success of information system implementation often depends on how users experience the benefits and ease of use. This research aims to investigate the influence of perceived Usefulness and ease of use on the quality of information systems through user satisfaction.Methodology/approach: This research is quantitative research with data collection techniques through surveys. The population of this research is all regional apparatus in Palopo City that uses the Regional Apparatus Information System (SIPD). The sample that will be used as respondents is 50 SIPD managers or users. The collected data was analyzed descriptively and correlationally using SmartPLS.Results/findings: The research results show that perceived benefits have a positive and significant influence on system user satisfaction. Ease of use have a positive and significant influence on user satisfaction. User satisfaction have a positive and significant effect on system quality. Perceived benefits have a positive and significant influence on system quality. Ease of use have a positive but not significant influence on system quality. Perceived benefits have a positive but not significant influence on system quality through user satisfaction. Ease of use have a positive and significant effect on system quality through user satisfaction.Conclusions: User satisfaction significantly impacts system quality, influenced by perceived benefits and ease of use. Ease of use directly affects satisfaction, while its impact on quality is limited. Perceived benefits mediate satisfaction and system quality.Limitations: The analysis of this study still requires other more in-depth variables such as benefit, actually and smart by a function of system information management to get more in-depth measurement results.Contribution: The theoretical implications of this study emphasize the necessity of preserving user SIPD to ensure effective governance.Keywords: Ease Of Use, Information System Quality, Perceived Benefit, User SatisfactionHow to Cite: Pirham, S., Khaddapi, M., Rahmawati. (2025). Association of Perceived Benefits and Ease of Use on Quality of Palopo City Government Information System Through User Satisfaction. Studi Ilmu Manajemen dan Organisasi, 6(1), 21-38.